PENINGKATAN HASIL BELAJAR TEMATIK TERPADU TEMA 3 MENGGUNAKAN MODEL SAVI DI KELAS V SD - Rahmi, Yulia; Sukma, Elfia; Aztimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe research is aimed to describe the improvement of the students’ learning outcomes  in thematic integrated to theme 3 by using Somatic Audiotory Visual Intellectual model at 5 thgrade of Elementary School. The research is The classroom action research and conducted in the research by using both qualitative and quantitative approaches. By using three cycles to the covering four stages: planning, implementation, observation, and reflection. The subject of the research were the teacher and 28 students of SDN 13 Lubuk Alung, 14 male students and 14 female students. The result of research shows that Somatic Audiotory Visual Intellectual model has improved the students’ learning outcome in thematic integrated learning in elementary school.          Keywords: Learning Outcomes, Somatic Audiotory Visual Intellectual